The strongly damped baroclinic response to wind in a multibasin reservoir. (14th June 2013) - Imam, Yehya E.; Laval, Bernard; Pieters, Roger; Lawrence, Gregory
Abstract : Field data and a forced, modal‐based, two‐layer, variable‐cross‐section model (TLVC) were used to examine the baroclinic response to wind in a large multibasin reservoir, Nechako Reservoir (British Columbia, Canada). The TLVC showed that most of the thermocline deflections at the dam could be accounted for by considering the first two basins upstream of the dam, Knewstubb and Natalkuz Lakes, and that the thermocline deflections were dominated by the first (H1) and second (H2) horizontal baroclinic modes of the combined basins. Calibration of the TLVC against the field data showed that the H1 and H2 modes were strongly damped, with effectively no free thermocline oscillations. This strong damping had two effects: high coherence between the wind and thermocline deflections and phase lags between thermocline deflections at different locations. The damping in Nechako Reservoir is stronger than in many lakes, and results from both high velocities within the geometric constriction between Knewstubb and Natalkuz Lakes and drag due to submerged trees, which cover 30% of the bed. Our study provides a picture of overdamped baroclinic response and shows how useful information about the baroclinic response in complex bathymetries can be obtained using relatively simple tools such as the TLVC.